Bacterial profiles and antibiotic susceptibility pattern in patients with chronic dacryocystitis - Aşgın, Nergis; Çakmaklıoğulları, Murat (Journal of Surgery and Medicine, 2020)
Aim: Dacryocystitis is an infection of the lacrimal apparatus, and without appropriate treatment, it can lead to serious complications such as orbital cellulitis and meningitis. In this study, we aimed to determine the frequency and antibiotic susceptibility of the bacterial pathogens in chronic dacryocystitis. Methods: This cross-sectional study included 60 patients diagnosed with chronic dacryocystitis in the Ophthalmology department of Karabuk Training and Research Hospital between December 2019 and February 2020. Aerobic culture tests were performed using swab samples obtained from the lacrimal punctum of the patients. Identification and antibiotic susceptibility of isolates were determined using Phoenix-100TM (Becton Dickinson, Sparks, MD, USA) fully automated system. Results: In total, 43 of 60 (71.7%) of patients were females, and the mean age was 56.78 (12.67) years. Aerobic bacteria were isolated from 51 (85%) of 60 samples. The most common pathogens were Pseudomonas aeruginosa (45%), Staphylococcus epidermidis (15.7%), and Staphylococcus aureus (11.8%) respectively. The most effective antibiotics against Gram-negative bacteria were aminoglycosides with a susceptibility of >90%. Gentamicin was also active against 85.7% of Gram-positive bacteria. Although in-vitro efficacy of ciprofloxacin was 81.5% against Gram-negative bacteria, it was mildly active against Gram-positive bacteria (52.5%). Methicillin resistance was detected in 33% of Staphylococcus species. Conclusion: In our region, aminoglycosides may be preferred instead of fluoroquinolones for the empirical treatment of chronic dacryocystitis. However, since our study is single-centered and small-sized, these findings should be supported by large-scale studies in the future.